ANALYSIS OF DELAYS IN EMOTIONAL DEVELOPMENT AND INDEPENDENCE OF CHILDREN AGED 5-6 AT RA ZAYYAD AZ-ZAHRA TEMBELOK - Linda Atika Dewi (JOETAL: Journal of Education, Teaching and Learning, 2025)
The purpose of this study was to determine the emotional development and independence of children aged 5-6 and the causes of delays in emotional development and independence in children aged 5-6 at RA Zayyad Az-Zahra Tembelok. This study used a qualitative descriptive approach. Data collection techniques used three methods: observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and verification. Data validity was checked through diligent observation and triangulation. Based on research conducted by researchers at RA Zayyad Az-Zahra Tembelok, the emotional development and independence of children aged 5-6 years were determined. Three children (AY, KAT, and M) were not yet fully developed emotionally, such as not being able to control their feelings, not being able to demonstrate self-confidence, not being able to understand rules and discipline, not being able to share, help, and assist friends, and not being able to show empathy. Meanwhile, in terms of independence, they were not yet able to tie and untie their own shoelaces, eat and drink independently, use the toilet independently, and do their own homework. Factors contributing to delays in emotional development include learning experiences, learning by imitation, and environmental factors. Factors contributing to delays in independence include parenting styles, gender, and genes/heredity.